Actinobacillus succinogenes ATCC 55618 Fermentation Medium Optimization for the Production of Succinic Acid by Response Surface Methodology. (3rd October 2012) - Zhu, Li-Wen; Wang, Cheng-Cheng; Liu, Rui-Sang; Li, Hong-Mei; Wan, Duan-Ji; Tang, Ya-Jie
Abstract : As a potential intermediary feedstock, succinic acid takes an important place in bulk chemical productions. For the first time, a method combining Plackett-Burman design (PBD), steepest ascent method (SA), and Box-Behnken design (BBD) was developed to optimize Actinobacillus succinogenes ATCC 55618 fermentation medium. First, glucose, yeast extract, and MgCO3 were identified to be key medium components by PBD. Second, preliminary optimization was run by SA method to access the optimal region of the key medium components. Finally, the responses, that is, the production of succinic acid, were optimized simultaneously by using BBD, and the optimal concentration was located to be 84.6 g L −1 of glucose, 14.5 g L −1 of yeast extract, and 64.7 g L −1 of MgCO3 . Verification experiment indicated that the maximal succinic acid production of52.7 ± 0.8  g L −1 was obtained under the identified optimal conditions. The result agreed with the predicted value well. Compared with that of the basic medium, the production of succinic acid and yield of succinic acid against glucose were enhanced by 67.3% and 111.1%, respectively. The results obtained in this study may be useful for the industrial commercial production of succinic acid.